Global or adapted advertising? Consumer evaluation of advertising activity of foreign enterprises on the Polish market - Robert Nowacki (Contemporary Economics, 2021)
Intensification of globalization processes in the contemporary world entails conse-quences for all areas of socio-economic life. The latter concerns also advertising, which is particularly sensitive to the developments occurring in the global envi-ronment. Expansion into foreign markets presents enterprises with the dilemma of how to advertise their products and services. The specific question which appears in this context is whether to use standardized or adapted advertising. The attitude of the audience on the target market is of key importance. The present article also focuses on the impact of globalization on the recipients' perception of the adver-tising activity of foreign companies operating in the Polish market. Assessment of the degree of acceptance of foreign enterprises' standardized advertising activities on the Polish market, their attractiveness and impact on competitiveness, from the perspective of Polish consumers. The basis for the study are the findings of a sur-vey conducted in 2019 and 2020 on a sample of Polish consumers aged 15+ se-lected using the quota method. The subject of the research were opinions on advertising activities used on the Polish market by foreign companies, taking into account the differentiation into global and adapted advertising. The respondents assessed the level of attractiveness and acceptance of activities related to advertis-ing standardization procedures. The results of the research indicate that Polish consumers perceive the globalization of advertising and have mixed feelings about it. On the one hand, they appreciate the attractiveness of standardized advertise-ments, on the other, they assess their effectiveness as worse. However, the re-spondents also point out that they have a positive impact on the competitiveness of foreign companies. The perception of standardized advertising is generally not dependent on demographic characteristics. There is only a slight direct effect of age on the perception of attractiveness and effectiveness of standardized and adapted advertising.
Keywords: M37; M21; 330; Advertising; advertising perception; global and adapted advertising; foreign enterprises; attractiveness and competitiveness of advertising